PREEMPTIVE SELF-DEFENCE ON ISRAEL-HEZBOLLAH ARMED CONFLICT UNDER INTERNATIONAL LAW - Wiwilliem Rizki Limboto; Teddy Nurcahyawan (Jurnal Hukum Adigama, 2018)
The legalization of war has legitimized wars of “self-defence”. On January 18, 2015 on the Syrian side of the Golan Heights, Israel launched an airstrike that killed six Hezbollah fighters and an Iranian brigadier general, Mohammed Ali Allahdadi. Israel claims that it acted preemptively in order to preserve its existential security by implementing a defensive policy commonly dubbed as the “War Between Wars” policy, to disrupt Iran’s supply of advanced weaponry for Hezbollah. On the other hand, Hezbollah in its continuous defiance of United Nations Security Council Resolution 1701 claims that the aforementioned arms supply was meant to preserve Lebanon’s security against future Israeli aggression. The facts of the case presented certain legal issues, as to whether or not Israel’s airstrike towards Hezbollah constitute a legitimate self-defence and its permissibility under international law. This is a normative legal research, thus relies heavily on library research, the IRAC method was used in deciphering the issue. After careful considerations, by attributing the said airstrike with the preemptive strike theory, it has been found that Israel’s airstrike was not preemptive, but rather preventive in nature, and should have been illegal under international law. However, a just cause test was conducted on both sides, and it has been found that the odds are more in favor towards Israel than Hezbollah. Ultimately, the research concluded that although preventive warfare was deemed to be illegal under international law, Israel’s claim of self-defence was more likely to be permitted in the international arena than Hezbollah’s.